Randomized controlled trial of three burns dressings for partial thickness burns in children. Issue 5 (August 2015) - Gee Kee, E.L.; Kimble, R.M.; Cuttle, L.; Khan, A.; Stockton, K.A.
Highlights: Three burns dressings for partial thickness burns in children were compared. Wound re-epithelialization time was significantly faster in children treated with Mepilex Ag™. Dressings with silicone interfaces had significantly lower pain levels at dressing changes. No infections were detected for the course of the study. Abstract: Background: This study compared the effects of three silver dressing combinations on small to medium size acute partial thickness burns in children, focusing on re-epithelialization time, pain and distress during dressing changes. Method: Children (0–15 years) with clean, ≤10% total body surface area (TBSA) partial thickness burns who met the inclusion criteria were included in the study. Children received either (1) Acticoat™; (2) Acticoat™ with Mepitel™; or (3) Mepilex Ag™ dressings. Measures of burn re-epithelialization, pain, and distress were recorded at dressing changes every 3–5 days until full re-epithelialization occurred. Results: One hundred and three children were recruited with 96 children included for analysis. No infections were detected for the course of the study. When adjusted for burn depth, Acticoat™ significantly increased the expected days to full re-epithelialization by 40% (IRR = 1.40; 95% CI: 1.14–1.73, p < 0.01) and Acticoat™ with Mepitel™ significantly increased the expected days to full re-epithelialization by 33% (IRR = 1.33; 95% CI: 1.08–1.63, p ≤ 0.01) when compared to Mepilex Ag™. Expected FLACC scores in the Mepilex Ag™ group were 32% lower at dressing removal ( p = 0.01) and 37% lower at new dressing application ( p = 0.04); and scores in the Acticoat™ with Mepitel™ group were 23% lower at dressing removal ( p = 0.04) and 40% lower at new dressing application ( p < 0.01), in comparison to the Acticoat™ group. Expected Visual Analog Scale-Pain (VAS-P) scores were 25% lower in the Mepilex Ag™ group at dressing removal ( p = 0.04) and 34% lower in the Acticoat™ with Mepitel™ group ( p = 0.02) at new dressing application in comparison to the Acticoat™ group. There was no significant difference between the Mepilex Ag™ and the Acticoat™ with Mepitel™ groups at all timepoints and with any pain measure. Conclusion: Mepilex Ag™ is an effective silver dressing, in terms of accelerated wound re-epithelialization time (compared to Acticoat™ and Acticoat™ with Mepitel™) and decreased pain during dressing changes (compared to Acticoat™), for clean, <10% TBSA partial thickness burns in children.